2015
DOI: 10.17116/jnevro20151152216-20
|View full text |Cite
|
Sign up to set email alerts
|

Low contrast non-color vision in patients with multiple sclerosis

Abstract: The results demonstrated low-contrast vision dysfunction while high-contrast vision remained intact. The level of low-contrast vision in MS patients differed significantly from that in the controls. The higher severity of visual disturbances was identified during high illumination. The direct correlation between the degree of low-contrast vision dysfunction and the level of disability on EDSS was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Here, the significant decrease in the NAA/Cr ratio in the frontal NAWM may in part account for the phenomenon of cognitive deficits that occurs in most MS patients, and this has been demonstrated by previous studies. [ 36 39 ] For example, a global memory disorder involving indices for short-term memory, long-term memory, and working memory was found in MS patients in Staffen et al's study, [ 40 ] and deficits in decision-making under risk conditions, which might be related to deficits in processing speed or visuospatial learning, were found in MS patients in a study by Rovaris M and colleagues [ 41 ] Regarding NAA/Cr abnormalities in the parietal-occipital NAWM, Kotov et al's [ 42 ] work showed that they may be associated with vision impairment caused by MS.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the significant decrease in the NAA/Cr ratio in the frontal NAWM may in part account for the phenomenon of cognitive deficits that occurs in most MS patients, and this has been demonstrated by previous studies. [ 36 39 ] For example, a global memory disorder involving indices for short-term memory, long-term memory, and working memory was found in MS patients in Staffen et al's study, [ 40 ] and deficits in decision-making under risk conditions, which might be related to deficits in processing speed or visuospatial learning, were found in MS patients in a study by Rovaris M and colleagues [ 41 ] Regarding NAA/Cr abnormalities in the parietal-occipital NAWM, Kotov et al's [ 42 ] work showed that they may be associated with vision impairment caused by MS.…”
Section: Discussionmentioning
confidence: 99%